Menapaki Jalan Cinta Rabiah Al-Adawiyah dan Erich Fromm (Suatu Studi Komparasi) - Merita Dian Erina (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the problems in treading the path of love by Rabiah al-Adawiyah and Erich Fromm. The research method is used a qualitative method with descriptive and comparative analysis. The results of the study show that love is turning away everything except for those who are loved. Love is an active force within oneself that is able to break down the barriers between humans and others. For Rabi'ah love is the basis of servitude to Him. In his poems, he only focuses his love on God. In this love there are several elements that have been passed before, namely repentance, asceticism, patience, gratitude, wara 'and ridla. Meanwhile, Erich Fromm, love is a solution to overcome the sense of separation and alienation. Erich Fromm sees love in things that are often encountered in social life. Thus, he divides into five objects of love, namely brotherly love, motherhood, erotic love, self-love and God's love. In this love there are four elements, namely attention, responsibility, respect and knowledge. From this study it can be concluded that there are three similarities and differences between Rabi'ah and Erich Fromm. The three similarities are in terms of the background of life, the form of love and the sacrifices made for the happiness of the loved one. While the difference lies in the factors that cause love, objects and elements of love. This study recommends to all people to apply these two concepts of love so that they can achieve balance in worldly and ukhrawi life.